Politicians, bankers and the Great Depression: The Spanish banking crisis of 1931 - Enrique Jorge-Sotelo (The European Association for Banking and Financial History (EABH), 2022)
This paper contributes to the literature on moral hazard, lending of last resort and the political origins of banking crises. Drawing on newly accessed quantitative and qualitative archival sources the paper documents how a bank - Banco de Catalu\~na - formed a coalition with the Dictatorship of Primo de Rivera (1923-30) in order to depart from the framework of "constructive ambiguity" that characterized central bank lending of last resort in Spain. As a result, the bank developed a uniquely risky portfolio and incurred in insider lending to internationally exposed firms at the onset of the Great Depression. The fall of the Dictatorship and democratic transition, the collapse of international trade, and global deflation during 1929-31 made fragilities emerge causing the bank to fail.
Keywords: N24; E58; G01; 330; moral hazard; lender of last resort; Great Depression